2019
DOI: 10.1021/acs.jpcc.8b11716
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Au(I)–Thiolate Complexes through Aggregation-Induced Emission: The Effect of pH during and Post Synthesis

Abstract: Luminescent Au­(I)–thiolate complexes (Au­(I)–SR) are synthesized at room temperature using glutathione as both a reducing agent and capping ligand. The photoluminescence (PL) intensity and emission wavelength are found to be strongly affected by the pH environment during and post synthesis. Although there is no Au(0) core present in these complexes, Au­(I)–SR exhibit PL which can be further enhanced through an aggregation-induced emission mechanism. The structures of these Au­(I)–SR at each pH stage are caref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 53 publications
3
39
1
Order By: Relevance
“…(A), the GSH-AuNCs prepared in this work were spherical and in uniform size, which has a distinct lattice structure. The results of characterization and optical properties of GSH-AuNCs are consistent with the previous synthesis protocols, indicating that AuNCs were successfully prepared 28. …”
supporting
confidence: 87%
“…(A), the GSH-AuNCs prepared in this work were spherical and in uniform size, which has a distinct lattice structure. The results of characterization and optical properties of GSH-AuNCs are consistent with the previous synthesis protocols, indicating that AuNCs were successfully prepared 28. …”
supporting
confidence: 87%
“…Nevertheless, the origin of dual-emission band for Ag 1 Au@DT NCs and its pH-dependent PL emission remains elusive. In most cases, the pH-dependent fluorescence properties were generally observed for ligand-protected metal NCs with AIE characteristics ( Wu et al, 2019b ; Chang et al, 2017 ; Su and Liu, 2017 ), in which the pH value was deemed to alter the charge state of the protected ligand and inhibited the aggregation of the Au(I)-thiolate staple due to the electrostatic repulsion. In our case, the pH variation cannot be a trigger of AIE for Ag 1 Au@DT NCs because of the nonionic nature of alkylthiol (DT) protective ligands on the metal core surface.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, a well Au(0)@Au(I) core‐shell‐structured BSA‐AuNCs would form. The AuNCs as such have a high content of Au(I)‐BSA complexes in the shell and the luminescence can be ascribed to the LMMCT effect, leading to a boost of PL intensity …”
Section: Resultsmentioning
confidence: 83%
“…To date, several recent studies have been reported aiming to produce AuNCs with enhanced luminescence, and the mechanism behind high luminescence is now better explained . Among all of the explanations, increasing the content and aggregation degree of Au (I)‐thiolate complexes on the surface of Au(0) core has been widely accepted as an effective way to gain highly luminescent AuNCs through enhanced aurophilic interactions . Besides, AuNCs can undergo aggregation‐induced emission (AIE) mechanism that further enhances the PL intensity .…”
Section: Introductionmentioning
confidence: 99%